The impact of clinical pharmacists’ medication reconciliation upon patients’ admission to reduce medication discrepancies in the emergency department: a prospective quasi-interventional study - Heba Othman Shaker; Ahmed Abdel Fattah Sabry; Asmaa Salah; Gilan Mohamed Ragab; Nahla Ahmed Sedik; Zahraa Ali; Doha Magdy; Asmaa Mohamed Alkafafy (International Journal of Emergency Medicine, 2023)
Abstract Background The role of the clinical pharmacist in medication reconciliation is well established. Upon patients’ admission, the reconciliation service mainly focuses on achieving an accurate and full drug history. This will achieve the best treatment plan and reduce medication discrepancies. Upon the recent implementation of clinical pharmacy services in the emergency department at Alexandria Main University Hospital, medication reconciliation was one of the most important duties that needed to be focused on. We hypothesized that clinical pharmacists are able to achieve patients’ drug history lists with higher accuracy than emergency physicians. Results A total number of 161 patients were included. Age was 58.59 ± (13.78) years, number of comorbidities was 2.39 ± (1.22) and number of home medications was 4.51 ± (2.72). Clinical pharmacists’ fulfillment of patients’ drug history was significantly more accurate than the emergency physicians (75.16% and 50.3% of the total number of revised patients’ profiles respectively). The clinical pharmacists could put a written copy of the accurate patients’ drug history list in only 50.93% of the revised patients’ profiles. Five hundred eighty-five medication discrepancies were detected which represent an average of 3.63 discrepancies/medication sheet. Medications at Transitions and Clinical Handoffs (MATCH) Toolkit for medication reconciliation and the National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) index were used to categorize discrepancies. Categories A, B, and C represented (66.5%), while categories D, E, and F represented (33.5%) of the total discrepancies. There was a significant direct relationship between the total number of discrepancies and both the number of comorbidities and the number of drugs administered before hospital admission. Conclusion The clinical pharmacists are the main members of the emergency health care team. One of their fundamental services is medication reconciliation. The establishment of a complete drug history list and physicians’ discussion about the current treatment plan can obviously detect and reduce medication errors. Trial registration NCT04395443. Registered 16 May 2020.